BARRIERS OF FALL RISK ASSESSMENT AND PREVENTION IMPLEMENTATION IN HOSPITAL SETTING - Gading, Patrick William (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2018)
Falls are the most worrying incidence of patient safety concern that have an impact on injury and death. 1.9 to 3 percent of patients fall in the hospital, with injuries in 6 to 44 percent. Hospitals are making efforts to reduce those fall rates, but its implementation are hindered by a variety of barriers. This study aims to identify the barriers of fall risk assessment and prevention in the hospital. The research method is systematic review using PRISMA, with 15 included studies. Identified barriers includes insufficient knowledge, lack of motivation, absence of champion, lack of resources, inadequate communication, unsustainable program, and support and access shortage. To successfully implement fall prevention programs in hospitals requires a multifaceted, planned approach that includes: regular education and training for staff and patients; provision of equipment; audit, reminders and feedback; leadership and champions; simple programs; and a framework and time for adaptation in the hospital. Keywords: barriers, fall risk assessment, fall prevention, hospital